No-drain DIEP Flap Donor-site Closure Using Barbed Progressive Tension Sutures - Purushottam Nagarkar; Chrisovalantis Lakhiani; Angela Cheng; Michael Lee; Sumeet S. Teotia; Michel Saint-Cyr (2016)
The use of progressive tension sutures has been shown to be comparable to the use of abdominal drains in abdominoplasty. However, the use of barbed progressive tension sutures (B-PTSs) in deep inferior epigastric artery perforator (DIEP) flap donor-site closure has not been investigated.A retrospective chart review was performed on patients with DIEP flap reconstruction in a 3-year period at 2 institutions by 2 surgeons. Patients were compared by method of DIEP donor-site closure. Group 1 had barbed running progressive tension sutures without drain placement. Group 2 had interrupted progressive tension closure with abdominal drain placement (PTS-AD). Group 3 had closure with only abdominal drain placement (AD). Data collected included demographics, perioperative data, and postoperative outcomes.Seventy-five patients underwent DIEP reconstruction (25 B-PTS, 25 PTS-AD, and 25 AD). Patient characteristics-age, body mass index, comorbidities, smoking status, and chemotherapy-were not significantly different between groups. Rate of seroma was 1.3% (B-PTS = 0%, PTS-AD = 4%, AD = 0%), wound dehiscence 16% (B-PTS = 8%, PTS-AD = 16%, AD = 24%), and umbilical necrosis 5.3% (B-PTS = 0%, PTS-AD = 0%, AD = 16%). No hematomas were observed in any patients. No statistically significant difference was found between complication rates across groups.Use of B-PTSs for abdominal closure after DIEP flap harvest can obviate the need for abdominal drains. Complication rates following this technique are not significantly different from closure using progressive tension suture and abdominal drain placement. This practice can prevent the use of abdominal drains, which can promote patient mobility, increase independence upon discharge, and contribute to patient satisfaction.